Third language acquisition in adulthood - Cabrelli Amaro, Jennifer; Flynn, Suzanne; Rothman, Jason (Studies in bilingualism ;, 2012)
Research on the phonological acquisition of a third language (L3) is still in its infancy; therefore, the present contribution is intended to further investigate the area by focusing on the phenomenon of foreign accentedness and the widely disputed sources of cross-linguistic influence in L3 phonology. The study employs the technique of perceptual judgement of a foreign accent in a third language. It aims to determine whether trilingual speakers of typologically unrelated languages (i.e. L1 Polish, L2 French and L3 English) have a tendency toward L1- or L2-accented speech in L3 performance and.